Viver e contar : diários de uma tese sobre os Cadernos de Lanzarote, de José Saramago - Silva, Marcelo Brito da (2021)
This thesis, written as a research journal, proposes an analysis of José Saramago's journals, the Cadernos de Lanzarote, based on the concepts of autobiography, journal and intimacy as reading operators used by Clara Rocha, Georges Gusdorf, Bèatrice Didier, Leonor Arfuch, among other authors, and on the concept of an “autobiographical pact”, formulated by Philippe Lejeune, which assumes an identity among the real author, the narrator and the protagonist. In an approach that assumes the precariousness of representation, given that every word is always too little, this research seeks to map out, from the internal morphology of the work, the main uses that Saramago makes of the autobiographical genre, namely, the journal as a defense strategy, as an exercise of self-indulgence, as a catharsis of emotions and as a way of building a personal image, highlighting traits such as frontality, commitment, humility and skepticism. From a methodological point of view, this research is grounded on the idea of isomorphic criticism, proposed by Roland Barthes, in order to constitute journals about journals and, thus, an alignment of daffodils that allows the reader to find out revelations about the writer's and the researcher's personal experiences. As to theoretical references, the work contemplates the genealogy, characteristics and limits of journals as a genre, and it seeks to explain the biographical emphasis that characterizes our time.